2005
DOI: 10.1074/jbc.m504172200
|View full text |Cite
|
Sign up to set email alerts
|

The Binding Site in β2-Glycoprotein I for ApoER2′ on Platelets Is Located in Domain V

Abstract: The antiphospholipid syndrome is caused by autoantibodies directed against ␤ 2 -glycoprotein I (␤ 2 GPI). Dimerization of ␤ 2 GPI results in an increased platelet deposition to collagen. We found that apolipoprotein E receptor 2 (apoER2 ), a member of the low density lipoprotein receptor family, is involved in activation of platelets by dimeric ␤ 2 GPI. To identify which domain of dimeric ␤ 2 GPI interacts with apoER2 , we have constructed domain deletion mutants of dimeric ␤ 2 GPI, lacking domain I (⌬I), II (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(73 citation statements)
references
References 43 publications
3
69
1
Order By: Relevance
“…In selected experiments, the cells were treated with anti-β2GPI monoclonal antibody (FC1, 3F8, or 2aG4; 10 μg/ml). Additional experiments were performed in cells pretreated with recombinant monomeric β2GPI (apple 2-β2GPI, 1.5 μg/ml) or dimerized β2GPI (apple 4-β2GPI, 1.5 μg/ml), which were was constructed and expressed as described previously (15,38). Studies were also done to assess the role of LDLR family members in cells pretreated with GST-RAP or GST control (12 μg/ml for 15 minutes), which were purified as previously reported, and purity was confirmed by SDS-PAGE (36).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In selected experiments, the cells were treated with anti-β2GPI monoclonal antibody (FC1, 3F8, or 2aG4; 10 μg/ml). Additional experiments were performed in cells pretreated with recombinant monomeric β2GPI (apple 2-β2GPI, 1.5 μg/ml) or dimerized β2GPI (apple 4-β2GPI, 1.5 μg/ml), which were was constructed and expressed as described previously (15,38). Studies were also done to assess the role of LDLR family members in cells pretreated with GST-RAP or GST control (12 μg/ml for 15 minutes), which were purified as previously reported, and purity was confirmed by SDS-PAGE (36).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, we determined whether aPL-induced eNOS inhibition involves β2GPI, and if the process also requires an LDL receptor (LDLR) family member, particularly apoER2, which has the capacity to directly bind β2GPI (14,15). Complementary experiments evaluating eNOS activation and leukocyte-endothelial cell adhesion were performed to link changes in enzyme activity with alterations in a key endothelial cell function that contributes to both the proinflammatory and the prothrombotic actions of aPL (16).…”
Section: Introductionmentioning
confidence: 99%
“…Biochemical analysis has shown that domain V interacts with the first LDL type A (LA) module of LRP8. 109 Solution nuclear magnetic resonance spectroscopy has identified the residues in both LRP8 and domain V of ␤ 2 GPI that are perturbed when both proteins interact. 110 Interestingly, the epitope in domain V that interacts with LA1 of LRP8 involves several positively charged residues, including the positively charged patch of lysine residues that are essential for phospholipid binding.…”
Section: Attenuation Of the Activity Of The Autoantibodiesmentioning
confidence: 99%
“…This would be somewhat analogous to the antichromatin Ab/chromatin immune complex driving additional autoantibody production in an SLE murine model via a crosslinking mechanism involving TLR9 and the B-cell receptor. 99 Direct binding experiments, as have been performed to study the interaction between ␤ 2 -GPI and other receptors such ApoER2Ј, 100 annexin A2, 64 and GPIb␣, 27 are required to solidify the involvement of TLR4.…”
Section: Activation Of Autoreactive Cd4 T Cells Hypothesismentioning
confidence: 99%